Interdisciplinary diagnostics and dental treatment: clinical case report of a 13-year-old female patient - Damyanova, Dobrinka Mitkova; Angelova, Sirma Todorova; Ruseva, Yoana Rumenova (International Journal of Public Health Science (IJPHS), 2025)
The study was conducted at the Faculty of Dental Medicine, University Medical-Dental Center, Varna, Bulgaria, in 2023, with permission and informed consent from the parents and the patient. Patient K. Vl. Ts., 13 years old from the city of Varna, comes without complaints. The reason for the visit is a desire to consult an orthodontist and start orthodontic treatment. The patient had a hospital stay at the age of 8 due to an operation - adenoidectomy. PLI - Plaque index by Silness and Löe with a value equal to 1.58, which defines oral hygiene as satisfactory to poor. Exogenous prophylaxis was performed. Treatment of plaque-associated gingival inflammation with professional oral hygiene and application of fluoride varnish every 3 months. Treatment of dental caries is operative: Teeth 27, 36, 37, 47 - with caries occlusalis D 2-3, lesions - after minimally invasive operative treatment with a glass-ionomer cement (GIC) placed, a definitive filling was made with photo-composite and sealant application of the healthy pits and fossae of the fissure. Patients and their parents should be trained to practice excellent oral hygiene during orthodontic treatment in order to reduce the risk of developing dental caries.